Charismatic Female Leadership and Succession in Pesantren A Sociological Feminist Perspective - Khoiriyah; Ahmad Ali Riyadi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The increasing involvement of women in Islamic educational leadership has challenged the long-standing assumption that religious authority within pesantren is predominantly male. However, limited attention has been given to how female leadership is sustained and transferred across generations within Islamic boarding schools. This study aims to examine the construction of female religious authority and the process of leadership succession at Pondok Pesantren Zumrotuththolibin through a sociological feminist perspective. A qualitative case study design was employed, involving in-depth interviews, participant observation, and document analysis. Fifteen participants, including the nyai, prospective successors, administrators, teachers, students, and community members, were selected through purposive sampling. Data were analyzed using thematic analysis supported by triangulation and member-checking procedures to ensure credibility. The findings reveal that female leadership legitimacy is established through a combination of religious competence, moral authority, managerial capability, and community trust. The study further demonstrates that leadership succession is intentionally institutionalized through religious education, family mentorship, gradual delegation of responsibilities, and active involvement of future female leaders in pesantren management and community engagement. The regeneration of authority among the nyai’s daughters illustrates how female leadership can be reproduced beyond individual charisma and transformed into a sustainable institutional structure. From a sociological feminist perspective, these findings challenge patriarchal assumptions regarding religious leadership while demonstrating the compatibility of female authority with Islamic educational traditions. This study contributes to the literature on gender, religious leadership, and succession in Islamic educational institutions by providing empirical evidence of how female authority is constructed, legitimized, and sustained within contemporary Indonesian pesantren.